(untitled) (Research, Society and Development, 2022)
Auriculotherapy has been gaining visibility in the Western world as an innovative technique, being used as an integrative and complementary practice, combined with traditional therapies, to fight cancer. The present work aims to synthesize the scientific evidence about the benefits provided by auriculotherapy in the quality of life of cancer patients. This is an integrative literature review, using the descriptors of the Health Sciences Descriptors (DeCS) and Medical Subject Headings (MeSH) and search strategies: “Auriculotherapy” AND “Cancer”; “Auriculotherapy” AND “Cancer Patients” AND “Clinical Trial”, and their respective variations in English. As inclusion criteria, there are publications indexed in the bases 1) ScienceDirect, PubMed, SciELO and Google Scholar; 2) in English and Portuguese; 3) presence of randomized clinical trials with cancer patients who received auriculotherapy intervention; 4) articles published between 2003 and 2021. Studies with evidence of less than three by Jadad scores, articles in languages other than English or Portuguese and with animal experimentation were excluded. In the results, it was identified that auriculotherapy allows an improvement in the quality of life of individuals diagnosed with this condition, promoting the control of anxiety and pain, in addition to the adverse symptoms resulting from the disease and its treatment. Thus, through the analysis of the 10 articles, it was identified that auriculotherapy, when combined with drug therapy, is a safe and low-cost technique capable of effectively relieving cancer pain, in addition to improving sleep quality and reduce anxiety, fatigue and the amount of pain relievers used.